Decision problems for word-hyperbolic semigroups - Cain, Alan J. (2019)
project PEST-C/MAT/UI0144/2011 fellowship (IF/01622/2013/CP1161/CT0001). Part of the work described here was carried out during a visit by the first author to the University of St Andrews, which was funded by a London Mathematical Society Research in Pairs Grant (ref. 41410).